The Effect of Giving a Book of Digital Fables in Banjar Language on the Anxiety Level of Children with Cancer Undergoing Chemotherapy During the Covid-19 Pandemic - Anggraini, Safariah (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: Experience during chemotherapy is a factor in the incidence of anxiety in children. Anxiety that continues to increase in children who are hospitalized can have a negative impact on the healing process, psychological health, behavioral, cognitive and emotional development. Playing is one way that can be used to reduce children's anxiety. On this occasion, researchers are interested in making digital fables as a form of play therapy for cancer children undergoing chemotherapy.Method: The purpose of this study was to analyze the effect of giving a digital fable book in Banjar language on the anxiety level of children with cancer undergoing chemotherapy during the COVID-19 pandemic. This study uses a quasi-experimental design with a posttest control group design approach. The research sample was 60 children. Sampling using consecutive sampling technique. The statistical test used an independent sample t-test with a significance level of 0.05. Measurement of anxiety using modified measurements of ZSRAS and T-MAS and Visual Facial Anxiety Scale (VFAS).Results: Based on the results of the study, it was found that there was an effect of giving a digital fable book in Banjar language on the anxiety level of children with cancer who underwent chemotherapy, especially in the intervention group. The significance p-value is 0.001 with a 95% confidence interval of 2.515 – 9.418. There is a difference in the mean score of anxiety levels between the control group and the intervention group of 5.967.Conclusions: This digital fable book in Banjar language can be applied in children's care rooms as a form of play therapy so that it can help children meet the needs of their developmental stages, namely playing and learning even during hospitalization.